2022
DOI: 10.1590/1678-4324-2022210183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethephon Application on Fruit Quality at Harvest and Post-harvest Storage of Japanese Plum (Prunus salicina) cv. Fortune

Abstract: The objective of this work was to evaluate different concentrations of ethephon on Fortune plum ripening, also observing the effect of ethephon concentration on the fruit parameters of yield, soluble solids (SS), titratable acidity (TA), SS/TA ratio, firmness, wooliness, diameter, length, and average fruit mass at harvest and post-harvest. The experimental design was completely randomized with five treatments and four replications, each experimental unit consisting of four plants. The ethephon concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Upon application, ethephon breaks down into ethylene, which is rapidly absorbed by plant tissues, thereby stimulating the plant to produce even more ethylene through a positive feedback loop (Petri et al, 2016). Orchards that employ effective management techniques, such as the use of ethephon spraying, are able to achieve early harvesting of high-quality fruits (Marzouk and Kassem, 2011;Mohammed-Al-Saif et al, 2017 andCocco et al, 2022). Therefore, the purpose of this research was to assess the effectiveness of different concentrations of ethephon on the growth, maturity, and quality of banana fruits.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Upon application, ethephon breaks down into ethylene, which is rapidly absorbed by plant tissues, thereby stimulating the plant to produce even more ethylene through a positive feedback loop (Petri et al, 2016). Orchards that employ effective management techniques, such as the use of ethephon spraying, are able to achieve early harvesting of high-quality fruits (Marzouk and Kassem, 2011;Mohammed-Al-Saif et al, 2017 andCocco et al, 2022). Therefore, the purpose of this research was to assess the effectiveness of different concentrations of ethephon on the growth, maturity, and quality of banana fruits.…”
Section: Original Research Articlementioning
confidence: 99%
“…The exogenous application of plant growth regulators has been shown to play a role in fruit development and quality (Kumar et al, 2014). Ethephon (2chlorethylphosphonic acid), a plant growth regulator, has been shown to accelerate the growth and development of fruits and vegetables, ultimately enhancing the maturity and quality of harvested commodities (Shafiq et al, 2014;Jalili Marandi et al, 2014 andCocco et al, 2022). Ethylene is popularly known for its ripening action, though, it regulates various aspects of plant life cycle including flowering, fruiting, fruit growth, and fruit development (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ETH is used as a herbicide to remove weeds such as Messina creeper ( Ipomoea cairica ) and promote pineapple ( Ananas comosus ) production by inducing flowers [ 106 , 107 ]. Also, many studies have found that ET-induced phenomena, such as fruit ripening, are dependent on the dosage of ETH, which is very similar to natural ET [ 108 ].…”
Section: Ethephon Applications In Herbivory Studiesmentioning
confidence: 99%